2020
DOI: 10.1021/acs.jpcc.0c06078
|View full text |Cite
|
Sign up to set email alerts
|

SERS Spectra of the Pesticide Chlorpyrifos Adsorbed on Silver Nanosurface: The Ag20 Cluster Model

Abstract: Surface enhanced Raman scattering (SERS) experiments and quantum chemical calculations (using density functional theory) on the interactions of chlorpyrifos (CPF), which is an intensively used pesticide, with a roughed silver nanoparticle surface were thoroughly investigated to study the inherent molecular mechanism. Ligand−cluster interaction geometries show that the CPF molecule is mainly adsorbed on the silver surface via both S atom and pyridine ring involving a covalent Ag•••S coordination as well as van … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 82 publications
(143 reference statements)
11
29
0
Order By: Relevance
“…Although the SERS chemical enhancement mechanism has widely been studied by DFT approach, there are scarcely computational works on the SERS phenomenon of pesticides. Recently, Ngo et al analyze the SERS CE mechanism of the pesticide chlorpyrifos (CPF) adsorbed on the Ag 20 pyramidal cluster [40]. The authors reported that the Ag 20 model successfully reproduces the SERS spectra of CPF as well as the CE mechanism, and its adsorption configurations are in good agreement with the ones obtained by the periodic slab model.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Although the SERS chemical enhancement mechanism has widely been studied by DFT approach, there are scarcely computational works on the SERS phenomenon of pesticides. Recently, Ngo et al analyze the SERS CE mechanism of the pesticide chlorpyrifos (CPF) adsorbed on the Ag 20 pyramidal cluster [40]. The authors reported that the Ag 20 model successfully reproduces the SERS spectra of CPF as well as the CE mechanism, and its adsorption configurations are in good agreement with the ones obtained by the periodic slab model.…”
Section: Introductionmentioning
confidence: 85%
“…Characteristics of the Ag nanoparticles used in this study were previously presented elsewhere [40]. Field emission scanning electron microscopy (FE-SEM) (CZ/Mira II LMH Tescan, Czech) was used to determine the surface morphology of the AgNPs samples.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Raman enhancements of pyridine on an Ag electrode were measured and then analyzed with the aid of DFT calculations using the tetrahedral Ag 20 cluster as a model representing the silver nanoparticles [88]. More recently, similar approaches were also applied to probe the SERS phenomenon of the chlorpyrifos, which is a pesticide using the Ag 20 cluster as a model for the silver surface [89]. Likewise, the tetrahedral gold Au 20 cluster was also used as a model to validate the SERS spectrum of pramipexole molecules adsorbed on the gold surfaces [75].…”
Section: Sers Spectra Of 6mp On Gold Surfacesmentioning
confidence: 99%